Analisis Faktor-Faktor yang Mempengaruhi Kepemimpinan Destruktif dalam Sekolah - Dita Adinda Fitri; Abdul Fattah Nasution; Khairul Umam Nasution; Bunga Sari Siagian; Dio Anugrah Pratama (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2026)
This study aims to analyze the factors influencing the emergence of destructive leadership in schools. Destructive leadership is understood as leadership behavior that systematically harms the goals of the school organization, teacher well-being, and the educational work climate. This study used a library method with a descriptive qualitative approach, through the review and synthesis of various relevant scientific literature, both nationally and internationally. The analysis shows that destructive leadership in schools is influenced by three main factors: internal factors of the leader (characteristics and personality of the principal), follower factors (characteristics of teachers and education personnel), and factors of the school’s organizational environment. These three factors interact and reinforce each other, as explained in the toxic triangle theory. Destructive leadership negatively impacts teacher work motivation, the school’s organizational climate, and the quality of the learning process. Therefore, preventative measures are needed through strengthening the principal selection and development system, improving teacher professionalism, and creating a democratic and accountable school environment.